An analysis of spelling errors in English made by grades IV, V, and VI pupils of the Llorente Central School, Division of Eastern Samar - Alota, Fe Alde 1939- (Quezon City College of Education, University of the Philippines Diliman, 1969)
The study analyzed spelling errors in English gathered from 881 themes of 285 Grades IV, V, and VI pupils of the Llorente Central Elementary School, Division of Eastern Samar, which they wrote during the first semester of the school year 1967-1968. Analysis of the data shows that the influence of Samar-Waray pronunciation and orthography is responsible for 42.3 percent of all causes of spelling errors and consistently ranked in each grade as a possible cause of error.
Vita.
Thesis (M.Ed. Second Language Teaching)--University of the Philippines, Diliman.
Keywords: Spelling ability -- Philippines -- Llorente (Eastern Samar).; English language -- Philippines -- Llorente (Eastern Samar) -- Errors of usage; English language -- Study and teaching (Elementary) -- Philippines -- Llorente (Eastern Samar)